ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED PADA PERUSAHAAN ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Cicilia, Yuris Pradenka (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Cigarette regulations, excise tax increases and other regulations have led to the decline of the cigarette industry, but the large-scale cigarette company has persisted and become more lucrative, leading many foreign investors to target cigarette companies in Indonesia. Analysis of financial performance using EVA and MVA able to know the financial condition of a company that is useful for investors and companies. This study aims to assess the financial performance of cigarette companies listed in the Indonesia Stock Exchange for the period of 2013-2015 using Economic Value Added (EVA) and Market Value Added (MVA).The type of research is descriptive research. The population of this research is four cigarette companies, which are all selected as the sample, based on saturated sampling method, in which all members of the population are used as the sample. Data analysis method used is using EVA and MVA method.The results of research conducted on cigarette companies listed on the Indonesia Stock Exchange in 2013-2015, showed that PT Hanjaya Mandala Sampoerna Tbk, PT Gudang Garam Tbk and PT Wismilak Inti Makmur Tbk in 2013 to 2015 have a positive EVA value, while PT Bentoel Internasional Investama Tbk in 2013 to 2015 has a negative EVA value because NOPAT is lower than its capital cost due to the company's loss. In addition, the four ccigarette companies in 2013 to 2015 have a positive MVA value indicating that the company's financial performance is in good condition because the market value of equity is greater than its total equity capital.Keywords : EVA, MVA, Financial Performance